Copper metabolism in osteoarthritis and its relation to oxidative stress and ferroptosis in chondrocytes - Yu, Qingyuan; Xiao, Yanan; Guan, Mengqi; Zhang, Xianshuai; Yu, Jianan; Han, Mingze; Li, Zhenhua (Frontiers in Molecular Biosciences, 2024)
Ferroptosis, an iron-ion-dependent process of lipid peroxidation, damages the plasma membrane, leading to non-programmed cell death. Osteoarthritis (OA), a prevalent chronic degenerative joint disease among middle-aged and older adults, is characterized by chondrocyte damage or loss.Emerging evidence indicates that chondrocyte ferroptosis plays a role in OA development.However, most research has concentrated on ferroptosis regulation involving typical iron ions, potentially neglecting the significance of elevated copper ions in both serum and joint fluid of patients with OA. This review aims to fill this gap by systematically examining the interplay between copper metabolism, oxidative stress, ferroptosis, and copper-associated cell death in OA.It will provide a comprehensive overview of copper ions' role in regulating ferroptosis and their dual role in OA. This approach seeks to offer new insights for further research, prevention, and treatment of OA.